CNDP1 genotype and renal survival in pediatric nephropathies - Peters, Verena; Kebbewar, Moustafa; Janssen, Bart; Hoffmann, Georg F.; Schmitt, Claus P.; Schaefer, Franz; Wühl, Elke (The journal of pediatric endocrinology and metabolism, 2016)
Background: The risk of developing type II diabetic nephropathy (DN) is lower in patients carrying the CNDP1 Mannheim polymorphism (homozygosity for the five leucine repeat), resulting in decreased activity of the histidine-dipeptide metabolizing enzyme carnosinase. The role of CNDP1 in other nephropathies is still unknown.